Time-sculptures of terrifying ambiguity: staging 'inner space' and migrating realities in Analogue's Living Film Set. Issue 1 (2nd January 2017) - Jarvis, Liam
ABSTRACT: This article examines Analogue's Living Film Set, an interactive theatre piece which uses miniature film sets, multi-touch surface technology and live video feeds to reframe my semi-remembered memories from the mid-1980s as a collective participatory experience. Drawing on new wave novelist J. G. Ballard's notion of childhood memory as 'time-sculptures of terrifying ambiguity' [Ballard, J. G. 1963. "Time, Memory and Inner Space." J. G. Ballard website (originally published in The Woman Journalist Magazine ). Accessed August 6, 2015.http://www.jgballard.ca/non_fiction/jgb_time_memory_innerspace.html ], I will demonstrate how my childhood town of Shepperton has been overwritten in both Ballardian literary fiction and the incursion of cinematic artifice from the neighbouring activities of Shepperton Film Studios. I argue that the ambiguity of my recollections and the contamination of my lived history with 'prosthetic memories' [Landsberg, Alison. 2004. Prosthetic Memory: The Transformation of American Remembrance in the Age of Mass Culture . New York, NY: Columbia UP, 20–21.] has provided a creative space to re-enact the blended hyperreality of my early childhood through the work's intermedial form. I will conclude by examining how the shifting reality status of the media used within the performance intersects with the notion of 'time-sculptures' and problematises what Carol Martin [(2013). Theatre of the Real . Basingstoke: Palgrave Macmillan.] has identified as 'theatre of the real'.